Ethnic Dynamics in Northern Senatorial Zone, Taraba State, Nigeria: An Inter-Group Perspective - Bello Ali; Salihu Lawal (Spektra: Jurnal Ilmu-ilmu Sosial, 2024)
This paper, titled "Inter-Group Relations and Peace in the Northern Senatorial Zone, Taraba State, Nigeria: A Study of Ethnic Dynamics," explores the relationships among diverse ethnic groups in Taraba State's Northern Senatorial Zone. Utilizing qualitative methods, particularly a narrative research design, the study delves into the dynamics of coexistence and tensions among ethnic groups, with a focus on indigenous communities such as the Fulbe, Hausa, Jenjo, Mumye, Wurkun, and others. Data collection involved interviews, participatory observations, and contextual analysis of documentary sources.The findings underscore the rich cultural diversity of Taraba State, where Traditional religions, Islam, and Christianity coexist within localities, deeply rooted in family identities. Historical connections among ethnic groups, characterized by peaceful coexistence, have been disrupted since the creation of Taraba State, leading to ethno-religious conflicts influenced by factors such as ethnic superiority, religious sentiments, and economic disparities. Challenges identified encompass disunity, power struggles, ethnic identity concerns, and unfavorable government policies, revealing the intricate nature of inter-group relations in the zone. Addressing these challenges necessitates collaborative efforts involving traditional, political, governmental, non-governmental, and religious entities. Recommendations to foster lasting harmony include increasing awareness and education, establishing dialogue platforms, promoting interfaith dialogue, empowering local communities, enhancing security measures, collaborating with NGOs, and conducting media sensitization campaigns to encourage responsible reporting and unity among diverse communities.